Pronunciation and Task-Based Instruction: Effects of a Classroom Intervention. (April 2021) - Gordon, Joshua
Explicit pronunciation instruction enhances production of intelligible, comprehensible, and fluent second language (L2) speech. Additionally, task-based instruction (TBI) enhances the production of segmentals and suprasegmentals, and promotes awareness of L2 forms in pronunciation. Since most previous research on TBI in L2 pronunciation learning has been carried out in laboratory settings, it is necessary to investigate how the implementation of tasks that differ in complexity in actual classroom settings could benefit L2 pronunciation learners. This classroom-based study investigated the effects of combining focus on form and TBI in L2 pronunciation instruction in the production of comprehensible, fluent, and L2-accented speech in English-as-a-foreign-language learners. Although the results of the study present modest gains, they make a case for the inclusion of explicit pronunciation instruction and tasks that differ in complexity to help learners develop pronunciation skills. Responding to recent calls for more classroom-based research that demonstrates how pronunciation can be implemented in systematic and principled ways, the results of this study are discussed in terms of implications and pedagogical recommendations for L2 pronunciation teaching and learning.